Peran Guru Pendidikan Jasmani dalam Merancang dan Menerapkan Program Latihan yang Efektif untuk Meningkatkan Keterampilan Fisik, Kesehatan, dan Perkembangan Siswa MI di SD Negeri 060913 Medan Tembung - Aprilyanti, Tarisyah Indah; Siregar, Khafifah Rahmawani; Noviyanti, Lathifah; Harahap, Tiara Indah; Suyono, Suyono (ALACRITY : Journal of Education, 2025)
This research aims to examine the role of education teachers in designing and implementing effective training programs to improve the physical skills, health and development of Madrasah Ibtidaiyah (MI) students at SD Negeri 060913 Medan Tembung. The main problem raised is how teachers can design training programs that suit students' needs and abilities and how the methods used can improve students' physical skills effectively. This research uses a qualitative approach with interview methods and direct observation of learning activities in Koper education classes. Data was collected through interviews with the sports teacher, Muhammad Fadli Azmi, and several students, as well as observations of the training activities carried out. The research results show that teachers use various training programs that focus on warm-up, games and coordination exercises according to the weekly theme. The methods applied, such as learning while playing, have proven to be effective in improving students' physical skills. Students' active involvement in sports activities is also obtained through a motivational approach and a variety of exercises. Teachers also provide constructive feedback to increase student enthusiasm. Suggestions for further research are to examine further the factors that influence the success of training programs as well as the influence of training programs on students' social and emotional development.